Doppler Parameters of Hepatic and Renal Hemodynamics in Patients with Liver Cirrhosis - D. Popov; R. Krasteva; R. Ivanova; L. Mateva; Z. Krastev (International Journal of Nephrology)
Introduction. There are limited studies on simultaneous evaluation of liver and renal blood flow using Doppler methods. We evaluated and compared the changes of liver and renal Doppler US parameters in patients with liver cirrhosis according to the degree of liver disease. Material and Methods. We assessed a large spectrum of liver and renal Doppler US parameters in 67 patients with liver cirrhosis. Results. Significant differences between Child’s classes or score, as well as MELD score, were observed in all investigated intrarenal blood flow Doppler US parameters, except renal artery peak systolic velocity, but only in some of the hepatic ones. The deviations of renal Doppler US parameters were also related with the complications of liver cirrhosis, as well as serum urea and creatinine levels. There was relationship between Doppler US parameters of hepatic artery and the corresponding renal artery Doppler US parameters. The changes of Doppler US parameters were age independent. Conclusion. Our results show, renal Doppler US parameters correlate with the severity and complications of liver cirrhosis. Because of dynamic deviations of renal Doppler US parameters with advance of liver cirrhosis, we recommend Doppler US of renal artery as a part of follow up of these patients.